2009
DOI: 10.1080/02713680902916090
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of MAPKs in Relation to Increased Intraocular Pressure in the Aqueous Humor of Rat Eye Injected with Hyaluronic Acid

Abstract: We suggest that these signaling molecules might be a new target for intervention, opening new possibilities for intraocular pressure management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…AqH is the optically clear fluid supplying the avascular tissues with oxygen, nutrients, antioxidants as well as carrying out waist products. AqH was reported to mediate mitogen-activated protein kinase signals, phosphatase and matrix metalloproteinases activation in TM cells [ 12 , 13 ]. AqH is produced by the non-pigmented ciliary epithelium (NPCE) of the ciliary processes and it has been hypothesized to convey signaling message between the ciliary epithelium tissue and the TM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…AqH is the optically clear fluid supplying the avascular tissues with oxygen, nutrients, antioxidants as well as carrying out waist products. AqH was reported to mediate mitogen-activated protein kinase signals, phosphatase and matrix metalloproteinases activation in TM cells [ 12 , 13 ]. AqH is produced by the non-pigmented ciliary epithelium (NPCE) of the ciliary processes and it has been hypothesized to convey signaling message between the ciliary epithelium tissue and the TM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active proteins [ 4 ] have been detected in the AH, supporting the idea of tissue communication within the drainage system. Among AH proteins, some were uniquely identified in the AH, while many others, such as cytokines [ 5 ], kinases [ 6 ], phosphatases [ 7 ], growth factors [ 8 ], are general participants of cellular communication. Further support for communication between the ocular drainage systems came from cell culture experiments where co-cultured non-pigmented ciliary epithelium (NPCE) and TM cells induced significant increases in the activity of some phosphatases and MMPs (matrix metalloproteinases ), MMP-2 and MMP-9,) in TM cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 In our previous studies we detected MAPK proteins in rat AH and showed that their expression levels were affected by the degree of IOP. 22 Although the sources for MAPK remained obscure, we speculated that phosphatases-the counterbalancing enzymes of these kinases-might be present in AH as well. Results of the present study confirmed this hypothesis and may contribute to the hypothesis of Coca-Prados and Escribano 37 that paracrine and autocrine effects within the anterior chamber might be mediated by the AH.…”
Section: Discussionmentioning
confidence: 99%
“…20 We previously suggested that serine/threonine kinases take part in AH outflow control 21 and showed that changes in MAPK protein expression and activation occur within the AH of a rat model of induced elevated IOP. 22 It was suggested that there is a close and direct signaling effect between redox state and kinase/phosphatase activity. 23 Dephosphorylation of specific phosphorylated sites can inhibit kinase activity.…”
mentioning
confidence: 99%